The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1992
DOI: 10.1227/00006123-199203000-00015
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Magnetic Resonance Imaging and Computed Tomography for Stereotactic Coordinate Determination

Abstract: The spatial accuracy of magnetic resonance imaging (MRI) has not been established for stereotactic surgery. Magnetic susceptibility artifacts may lead to anatomical distortion and inaccurate stereotactic MRI coordinates, especially when targets are in regions of the brain out of the center of the magnetic field. MRI-guided stereotactic localization, however, provides better multiplanar target resolution than is available with computed tomographic (CT) scanning. Therefore, we compared the accuracy of stereotact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(44 citation statements)
references
References 10 publications
1
41
1
1
Order By: Relevance
“…Indeed, it has been shown that the axis of the lead is slightly eccentric within the signal void [13], which can be as wide as 3.56 ± 0.3 mm [15], resulting in errors in the reconstruction of the electrode in the stereotactic space. Studies that compared contact localizations on postoperative MRI versus registration between preoperative MRI and postoperative CT scan found an error between 1.2 ± 0.86 mm [2] and 2.09 ± 1.79 mm [11], which is quite in the same range or slightly higher than our results. Finally, anatomical localization of the DBS lead contacts in the stereotactic space remains difficult to assess and has to be coupled with the clinical testing of the different contacts.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Indeed, it has been shown that the axis of the lead is slightly eccentric within the signal void [13], which can be as wide as 3.56 ± 0.3 mm [15], resulting in errors in the reconstruction of the electrode in the stereotactic space. Studies that compared contact localizations on postoperative MRI versus registration between preoperative MRI and postoperative CT scan found an error between 1.2 ± 0.86 mm [2] and 2.09 ± 1.79 mm [11], which is quite in the same range or slightly higher than our results. Finally, anatomical localization of the DBS lead contacts in the stereotactic space remains difficult to assess and has to be coupled with the clinical testing of the different contacts.…”
Section: Discussionsupporting
confidence: 55%
“…This method has been thoroughly compared to the localization of the lead on a postoperative MRI and is considered as acceptable to document the anatomic location of the electrode active contacts [1, 2, 5-10]. However, this technique introduces an error factor inherent with registration of two imaging modalities [11-13] and its results depend on the registration algorithm. As many surgical planning software programs are available, with different registration algorithms and for some of them an automatic lead detection device, we raised the question of the reproducibility of the results between software programs and aimed to compare the location of electrode contacts between four widely used planning devices.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the electrode tip center is thus rendered difficult, especially in vertical planes. In addition, the anatomical distortion on MRI created by susceptibility artifacts [15,16] may render measures in proximity to the electrode less reliable and explain differences in regard to CT. On the other hand, CT reformations in coronal and sagittal planes imply the risk of artifacts (particularly step artifacts) harboring inaccuracies concerning measures realized in those planes. One drawback of our study was the non-homogeneous CT acquisition protocol (with slice thickness varying between 0.6 and 1.25 mm), although measures realized on images with thicker slices did not show greater errors.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it is generally agreed that an increased distance to the isocenter is associated with increased image distortion [12,14,19,20]. However, it is important to identify the main vector that causes the deviation.…”
Section: Discussionmentioning
confidence: 99%